Wild DFW: Explore the Amazing Nature in and Around Dallas-Fort Worth - Keller, Harold W. (Journal of the Botanical Research Institute of Texas, 2023)
Wild DFW explores the natural wonders of the Dallas-Fort Worth area and highlights a paradise of places, plants, and animals if you know where to look for them. The book begins with Natural History and Ecology divided up into one- or two-page vignettes titled Wild Dallas-Fort Worth, East-West, Natural Dallas, Natural Fort Worth. Each area is described in general ecological terms without giving the scientific names of the plants and animals but leaving the reader with a sense of wonder of native prairies, forests, and riparian habitats.